AN ANALYSIS OF LAND RIGHTS MORTGAGE FROM A CIVIL LAW PERSPECTIVE - Wati, Tri Anika; Yahman, Dr. Yahman; Karim, Dr. Karim (jfpublisher, 2024)
Land is one of the natural resources controlled by the state and used for the benefit and prosperity of the people, as stipulated in Article 33 Paragraph (3) of the 1945 Constitution. The various land rights referred to in Article 4 of Law No. 5/1960 on the Basic Regulation of Agrarian Principles (UUPA) are further regulated in Article 16 Paragraph (1) of the UUPA, which are temporary land rights. One of the temporary land rights is a land mortgage. Based on this temporary characteristic, the researchers conducted research on agricultural land mortgage disputes. Based on the brief analysis mentioned previously, the researchers analyzed Decision Number: 20/Pdt.G/2021/PN.Blk which relates to the mortgage of land rights. This research uses a normative juridical approach by examining theories, concepts, legal principles, and regulations that are closely related to this research based on primary legal materials. The research method used is the literature method, because it requires the study of documents such as books and laws and regulations relating to the provisions and legal rules in the implementation of a land title pawn as a mortgage. The process of encumbering mortgage rights under Law No. 4/1996 involves three stages: a promise to grant Mortgage Rights, the granting of Mortgage Rights before a Land Deed Official (PPAT), and registration at the local land office. In Decision Number 20/Pdt.G/2021/PN, the plaintiffs were granted ownership of the disputed land, but the court did not rule on their claim regarding losses due to the defendant's unlawful possession after the pledge period expired.